Notes on the legal status of non-EU foreign workers in Spain. - Tarabini-Castellani Aznar, Margarita (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The object of this study is to analyze «grosso modo» the legal status of foreign workers from third countries, paying special attention to foreigners without a work permit. For reasons of space, I will only point out those issues which deserve greater attention and those which I have found of particular interest.